PENGARUH PENGALAMAN SEBELUMNYA DAN PENGETAHUAN PRODUK TERHADAP PERILAKU BERALIH MEREK PRODUK LAPTOP YANG DIMEDIASI FAKTOR KEPUASAN - Oscar Septiano, 09.05.51.0047 (Students Journal of Economic and Management, 2013)
There are factors that influence consumer brand switching behavior . Factors that may influence brand switching behavior are prior experience, product knowledge, satisfaction, media search , and retailers search. For marketers, if these factors treated properly, it can be directed to influence consumers brand switching behavior so they will choose their products/brands . This study want to examine the relationship between prior experience, product knowledge, and satisfaction related to consumer brand switching behavior of laptop products. Samples were taken from the students of the Faculty of Economics, University Stikubank Semarang . Engineering sample selection was purposive sampling. The steps are performed in the sampling technique is distributing questionnaires to students who have been long enough to have the product and use a laptop, and they switch the brand in the purchase of laptop products . To test the quality of the data the researcher use validity and reliability test . Meanwhile, to answer the research hypothesis used regression analysis, F test, t-test, R2 , and path analysis . Results of this study indicate that prior experience have positive and significant effect on satisfaction , product knowledge havepositive and significant effect on satisfaction, prior experience have positive and significant effect on the behavior of brand switching, product knowledge have positive and significant impact on brand switching behavior, satisfaction has a positive effect but not significant enough to brand switching behavior. Factor of prior experience, product knowledge, and satisfaction together or simultaneously influence brand switching behavior. Path analysis showed that the relationship between the variables of previous experience and knowledge of the product with variable switching brands is a direct relationship, and satisfaction variable isnot a mediating variable. Keywords : Prior Experience, Product Knowledge, Satisfaction, Brand Switching Behavior on Laptop Product